Knowledge, Attitude and Practice of Primary Care Physicians in Dealing with Acute Stroke in Indonesia - Putu Jaya Kusuma, - (Prince of Songkla University, 2021)
Objective: There are still many things that interfere with the practice of effective acute stroke management, with one of them being the failure of health workers providing appropriate management. Hence, this study was conducted to evaluate the level of knowledge, attitude and practices of primary care physicians (PCPs) in acute stroke management in Indonesia. Material and Methods: This cross-sectional face-to-face survey was conducted among all PCPs, from 63 primary health care centres; from October, 2019 to January, 2020 in Surabaya, Indonesia. A self-designed questionnaire, consisting of 25 questions, based on several guidelines, was used as the instrument of this survey. Results: In total, 134 PCPs participated. The majority of their level of knowledge obtained was in the moderate category (51.5%), while the majority of their attitude and practices towards stroke were in the good category (67.9% and 75.2%). Nearly 75.0% of PCPs also knew about thrombolytic therapy, but only <50.0% knew the ‘golden period’ of thrombolytic therapy. A significant correlation was found between PCPs knowledge-attitude (p-value<0.001), knowledge-practices (p-value=0.002) and attitude-practices (p-value<0.001). There was also a significant difference in the level of stroke knowledge between PCPs, with different clinical practice experience (p-value=0.015). Better stroke knowledge tended to be obtained by PCPs with younger clinical practice experience. Conclusion: The level of knowledge, attitude and practices of PCPs in acute stroke management in Indonesia is good, but should still be improved; especially knowledge about the use of thrombolytic therapy and its ‘golden period.’